Complement activation products in acute heart failure: Potential role in pathophysiology, responses to treatment and impacts on long-term survival. Issue 4 (1st June 2018) - Trendelenburg, Marten; Stallone, Fabio; Pershyna, Kateryna; Eisenhut, Timo; Twerenbold, Raphael; Wildi, Karin; Dubler, Denise; Schirmbeck, Lucia; Puelacher, Christian; Rubini Gimenez, Maria; Sabti, Zaid; Osswald, Luca; et al.
Abstract: Background: Previous studies have indicated a correlation between heart failure, inflammation and poorer outcome. However, the pathogenesis and role of inflammation in acute heart failure (AHF) is incompletely studied and understood. The aim of our study was to explore the potential role of innate immunity – quantified by complement activation products (CAPs) – in pathophysiology, responses to treatment and impacts on long-term survival in AHF. Methods: In a prospective study enrolling 179 unselected patients with AHF, plasma concentrations of C4d, C3a and sC5b-9 were measured in a blinded fashion on the first day of hospitalisation and prior to discharge. The final diagnosis, including the AHF phenotype, was adjudicated by two independent cardiologists. Long-term follow-up was obtained. Findings in AHF were compared to that obtained in 75 healthy blood donors (control group). Results: Overall, concentrations of all three CAPs were significantly higher in patients with AHF than in healthy controls (all p < 0.001). In an age-adjusted subgroup analysis, significant differences could be confirmed for concentrations of C4d and sC5b-9, and these parameters further increased after 6 days of in-hospital treatment ( p < 0.001). In contrast, C3a levels in AHF patients did not differ from those of the control group in the age-adjusted subgroup analysis and remained constant during hospitalisation. Concentrations of C4d, C3a and sC5b-9 were significantly higher when AHF was triggered by an infection as compared to other triggers ( p < 0.001). In addition, CAP levels significantly correlated with each other ( r = 0.64–0.76), but did not predict death within 2 years. Conclusions: Activation of complement with increased plasma levels of C4d and sC5b-9 at admission and increasing levels during AHF treatment seems to be associated with AHF, particularly when AHF was triggered by an infection. However, CAPs do not have a prognostic value in AHF.